Survey of trustworthy pervasive social networking - Zheng YAN; Chen-zi WU; Wei FENG; Zi-long WANG (网络与信息安全学报)
Trust plays an important role in pervasive social networking (PSN) for reciprocal activities among strang-ers.It helps people overcome perceptions of uncertainty and risk and engages in trust-related social behaviors.The current literature on trust management in PSN was reviewed.The advantages and disadvantages of existing solutions were analyzed.Furthermore,key research issues were presented.A research model was also proposed to achieve trustworthy pervasive social networking comprehensively.